CAN REFLECTION ENABLE TEACHERS TO PROVIDE A MORE HUMANE LEARNING PROCESS? - Reza Pahlevi; Lena Nurfadillah; Nurhadianty Rahayu; Dian Ikawati (English Didactic, 2022)
This study aims at exploring the practice of teachers’ reflection as a potential medium to disentangle the rigid teaching and learning interactions where teachers take control or dominate learning discourses. Utilizing the qualitative method of narrative inquiry, this study offers insight into how teachers’ reflective practices can set the ground for more humane pedagogic practices for students to express their voices in learning. The stories from two teachers contribute to a deeper understanding of how the simple acts of reflection can deconstruct the rigid teachers-learners interactions and create opportunities for a more collaborative and equal position of knowledge-sharing practices between teachers and learners.